Neurology a Queen Square textbook - Clarke, Charles; Howard, Robin; Rossor, Martin; Shorvon, Simon (Wiley-Blackwell, 2009)
This practical and attractive text takes the reader from a background of clinical medicine to the forefront of clinical neurological practice. Positioned between large encyclopedic multi-volume textbooks and short student texts to focus on clinical practice, this new book contains useful information presented in an easy to read style.